RESEARCH OF THE QUANTITATIVE RELATIONSHIP BETWEEN THE STRESS AND MAGNETIC OF Q235B ROUND HOLE SPECIMEN - ZHANG Ying; GAO Han; ZHANG ShengYu; LI Bin (Jixie qiangdu)
The paper adopts the testing technology of magnetic memory,and tests the Q235 B round hole specimen the leakage magic field around the round hole during the stretching process,to achieve the leakage magic field parametric distribution around the round hole in different loading stages. As the test specimens reached the specimen tensile strength,three kinds of pore size specimens take on the phenomenon that normal component value has greatly increased and the normal component of the gradient has suddenly changed in the local peak stress. This phenomenon proves that the magnetic memory method can forecast the stress concentration area. Meanwhile,according to the quantitative relationship between stress and magnetic in the peak position,and get the magnetoelastic effect irreversible component λHof Q235 B material under the experimental conditions,to provide the reference for the study of quantitative relation between local stress and magnetic memory characteristic value.